The Tradition of Ketipat Kawulu Ceremony in Hindu Community Civilization in Mataram City - Ni Komang Wiasti (Jurnal Syntax Admiration, 2024)
This research aims to: 1) To analyze the form of the Ketipat Kawulu Ceremony Tradition in Hindu Civilization in Mataram City, 2) To describe the function of the Ketipat Kawulu Ceremony Tradition in Hindu Civilization in Mataram City, 3) To analyze the meaning contained in the Ketipat Kawulu Ceremony Tradition in Hindu Civilization in Mataram City. The data collection techniques used in this research are 1) Observation, 2) interviews and 3) Documentation. Furthermore, the theories used to analyze are: 1) Religious Theory, 2) Symbolic Instruction Theory, and 3) Value Theory. The results of this study are: 1) The tradition form of ketipat kaulu ceremony in the civilization of Hindu Society in Mataram City consists of: a) carried out by the Hindu community in Mataram City; b) the place of the ceremony is focused on sanggah/merajan, dadya temple, beach and the nearest temple in Mataram City; c) this ceremony is held on tilem sasih kaulu; d) In this ceremony using banten tipat sirikan; e) Steady belief (sradha bhakti). 2) The function of the Ketipat kawulu Ceremony Tradition in Hindu Civilization in Mataram City, namely: a) Neutralizing negative forces; b) As an Implementation of Vedic Teachings; c) As an Actualization of Panca Yadnya; d) As a Practice of Tri Hita Karana teachings; e) Environmental Preservation. 3) The meanings contained in the implementation of the ketipat kaulu ceremony tradition in the civilization of Hindu society in Mataram City include the following: a) philosophical meaning; b) religious meaning (tattwa); c) social meaning d) cultural meaning; e) welfare meaning.